1974
DOI: 10.2466/pr0.1974.35.3.1305
|View full text |Cite
|
Sign up to set email alerts
|

Own vs Provided Constructs in a Reptest Measure of Cognitive Complexity

Abstract: Both cognitive complexity and cognitive differentiation scores calculated using own vs provided constructs were significantly correlated over treatments, but the two indices were independent of each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…In fact, Bannister and Mair (1968) argued that "the procedure of supplying adjective labels has become more widely favoured than can be theoretically or experimentally justified" (p. 67). This notion is consistent with the conclusion of Metcalfe (1974) that "while provided constructs can afford adequate data [for measures of cognitive complexity], preference should be given to the use of own constructs" (p. 1306).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In fact, Bannister and Mair (1968) argued that "the procedure of supplying adjective labels has become more widely favoured than can be theoretically or experimentally justified" (p. 67). This notion is consistent with the conclusion of Metcalfe (1974) that "while provided constructs can afford adequate data [for measures of cognitive complexity], preference should be given to the use of own constructs" (p. 1306).…”
Section: Discussionsupporting
confidence: 82%
“…One explanation concerns differences in the content of the provided and personal constructs themselves, whereas the other involves the actual process of construct elicitation. With regard to construct content, several authors have discussed the consequences of using provided versus elicited constructs in the investigation of cognitive structure (e.g., Adams-Webber, 1979; Kuusinen & Nystedt, 1975a, 1975b; Metcalfe, 1974; Neimeyer, 1988). Although results of some of these studies confirmed the functional similarity of provided and elicited constructs, results of several others have suggested the contrary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherents to Kelly's (1955) original method of eliciting constructs have maintained strong allegiance to an idiographic tradition (Cochran, 1977(Cochran, , 1983a(Cochran, , 1983b(Cochran, , 1983c, whereas other researchers have maintained equal adherence to Bodden's (1970) preference for using provided construct dimensions (see Neimeyer, 1988, for a review). The former have traditionally justified their allegiance to the method of eliciting constructs on the basis of preserving the personal meaning of an individual's constructions (Metcalf, 1974), whereas the latter have placed a premium on standardization and control of error variance. If replicated and extended, the present results may question both claims and qualify the usefulness of both positions.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring procedure, and the underlying logic of the measurement, is similar in these other versions; thus the remainder of this review will not distinguish these various species of Bieri's measure. Although some investigations have found these various versions not to correlate highly (e.g., Alban Metcalfe, 1974;Coleman, 1975;Tripodi & Bieri, 1963;Vacc & Vacc, 1973), we hope it will become clear that the evidence concerning Bieri's measure is rather univocal across the variations and hence that to distinguish the several species would only unnecessarily complicate matters.…”
Section: Alternative Measuresmentioning
confidence: 95%